2022
DOI: 10.5194/acp-22-2817-2022
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound fluxes over a winter wheat field by PTR-Qi-TOF-MS and eddy covariance

Abstract: Abstract. Volatile organic compounds (VOCs) contribute to air pollution through the formation of secondary aerosols and ozone and extend the lifetime of methane in the atmosphere. Tropospheric VOCs originate to 90 % from biogenic sources on a global scale, mainly from forests. Crops are also a potentially large yet poorly characterized source of VOCs (30 % of the VOC emissions in Europe, mostly oxygenated). In this study, we investigated VOC fluxes over a winter wheat field by eddy covariance using a PTR-Qi-TO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 140 publications
(164 reference statements)
0
4
0
Order By: Relevance
“…This is partly because the upward fluxes were dominated by a few major species (all of which have explicit CTM representation), and partly because of offsetting model errors between those major species. This work has provided a chemically detailed analysis of VOC surface-atmosphere exchange for one pine forest ecosystem, and builds upon a small number of similar studies that relied solely upon PTRMS (Loubet et al, 2022;Millet et al, 2018;Park et al, 2013). Further measurements employing multiple high-resolution mass spectrometers in different ecosystems are required to better understand surface-atmosphere VOC fluxes across the full suite of relevant compounds, diagnose the underlying environmental drivers, and advance the ability of current CTMs to capture the ensuing impact on atmospheric chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly because the upward fluxes were dominated by a few major species (all of which have explicit CTM representation), and partly because of offsetting model errors between those major species. This work has provided a chemically detailed analysis of VOC surface-atmosphere exchange for one pine forest ecosystem, and builds upon a small number of similar studies that relied solely upon PTRMS (Loubet et al, 2022;Millet et al, 2018;Park et al, 2013). Further measurements employing multiple high-resolution mass spectrometers in different ecosystems are required to better understand surface-atmosphere VOC fluxes across the full suite of relevant compounds, diagnose the underlying environmental drivers, and advance the ability of current CTMs to capture the ensuing impact on atmospheric chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (2013) performed detailed flux measurements over an orange orchard and detected 555 species contributing to the net VOC flux budget-with 10 commonly-known compounds making up 68% of the total flux. A recent study over a winter wheat field measured fluxes for 264 VOCs, with only four ubiquitous oxygenated VOCs accounting for 85% of total emissions (Loubet et al, 2022). A third study over a mixed temperate forest observed 377 VOCs with detectable surface-atmosphere exchange (Millet et al, 2018).…”
mentioning
confidence: 99%
“…The measurements made by the miniDOAS over the January 2020-June 2022 period (N = 16 888) show an average ammonia concentration of 2.23 µg m −3 in Paris over this period, with a standard deviation of 2.02 µg m −3 , indicating a high NH 3 variability. In comparison, the average concentration measured by the miniDOAS in an agricultural site at Grignon (Loubet et al, 2022) in September-October 2021 (France) is 6.52 ± 8.44 µg m −3 (Caville et al, 2023), almost 3 times higher than in Paris. The relatively low concentrations observed in Paris are explained by the distance to the major emission sources which are related to agricultural activities.…”
Section: Comparison Of Nh 3 Concentrations Between Iasi and Minidoasmentioning
confidence: 84%
“…Ion counts per second (cps) were computed by combining each ion peak. The cps were used to calculate the "uncalibrated" Chlorothalonil concentration following Loubet et al 74 using Toluene as a reference.…”
Section: Methodsmentioning
confidence: 99%